Infraestruturas de logística e transporte em Mato Grosso : uma leitura geográfica - Souza, Ronivalter de (2016)
The introduction of Brazil, in the new international division of labor brought about many changes in the national geographical space. The final economic integration of Brazil, under the aegis of globalization, was made possible by the expansion of the technicalscientific-informational environment, generously supported by the state, embodied in the artificiality of the territory, the modification of the natural environment for the actions of social groups which was enhanced to meet the demands of modern production required by the new logic of reproduction of capital. In this process, agricultural modernization was sharp and the agricultural frontier expanded, through the productive incorporation of outlying areas, especially the lands of Mato Grosso territory. The modernization of the agricultural sector resulted in increased production and the need for greater corporate fluidity, demanding more investment in the transportation sector. However, as the state had little capacity to provide the Mato Grosso area of logistics adequate transport to corporate interests, it created a framework that limits the competitiveness of the agribusiness chain, leading him to seek new possibilities for overcoming the existing difficulties